Efektivitas Penyaluran Bantuan Dana Kepada Masyarakat Korban Bencana Seroja Kota Kupang Berdasarkan Peraturan Pemerintah Nomor 22 Tahun 2008 - Bella Octavia Bole Padi; Saryono Yohanes; Hernimus Ratu Udju (International Forum of Researchers and Lecturers, 2023)
Natural disasters can happen anytime and anywhere without being predicted. The issue of natural disasters has a bad impact on many people, they can lose their lives and homes. The government in this case is directly in charge of handling this disaster case, namely the National Disaster Management Agency (abbreviated as BNPB) is a Non-ministerial Government Agency that has the task of assisting the President of the Republic of Indonesia in carrying out disaster management in accordance with the mandate of Law Number 24 of 2007 concerning Disaster Management. This research is a field research or empirical legal research, the methods used in data collection are interviews, observation and literature study, which was conducted in Nunbaun Delha Village and Manutapen Village, Alak District, Kupang City. Based on the results obtained by researchers based on the formulation of the problem of how far the effectiveness of the distribution of financial assistance to the victims of the seroja disaster in Nunbaun Delha Village and Manutapen Village, Alak District, Kupang City, is the problem of the initial initiative to establish a command post post, raising assistance, identifying the needs of victims. Factors inhibiting the effectiveness of the distribution of financial assistance to victims of the seroja disaster in Nunbaun Delha Village and Manutapen Village, Alak District, Kupang City Coordination and Information and Distribution of social assistance is not on time to recipients of social assistance.